Effects of free-air CO2 enrichment (FACE) and soil warming on CH4 emission from a rice paddy field: impact assessment and stoichiometric evaluation - Tokida, T.; Fumoto, T.; Cheng, W.; Matsunami, T.; Adachi, M.; Katayanagi, N.; Matsushima, M.; Okawara, Y.; Nakamura, H.; Okada, M.; Sameshima, R.; Hasegawa, T. (Copernicus GmbH, 2010)
Paddy fields are an important source of atmospheric CH4, the second most important greenhouse gas. There is a strong concern that the increasing atmospheric CO2 concentration ([CO2]) and global warming are further stimulating CH4 emissions, but the magnitude of this stimulation varies substantially by study, and few open-field evaluations have been conducted. Here we report results obtained at a Japanese rice free-air CO2 enrichment (FACE) site under water and soil temperature elevation during two growing seasons. Our objectives were to evaluate the effects of high [CO2] (ambient + 200 μmol mol−1) and elevated soil temperature (+ 2 °C) on CH4 emissions under completely open-field conditions. We found about 80% enhancement in total seasonal emissions by the additive effects of FACE and warming, indicating a strong positive feedback effect of global warming. The enhancement in CH4 emission from the FACE-effect alone (+ 26%) was statistically non-significant (P = 0.19). Nevertheless, observed positive correlations between CH4 emissions and rice biomass agreed well with previous studies, suggesting that higher photosynthesis led to greater rhizodeposition, which then acted as substrates for methanogenesis. Soil warming increased the emission by 44% (P < 0.001), which was equivalent to a Q10 of 5.5. Increased rice biomass by warming could only partly explain the enhanced CH4 emissions, but stoichiometric analysis of the electron budget indicated that even a moderate enhancement in organic matter decomposition due to soil warming can cause a large increase in CH4 production under conditions where Fe(III) reduction, which was little affected by soil warming, dominates electron-accepting processes. At later rice growth stages, advanced root senescence due to elevated temperature probably provided more substrate for methanogenesis. Our stoichiometric evaluation showed that in situ Fe reduction characteristics and root turnover in response to elevated temperature should be understood to correctly predict future CH4 emissions from paddy fields under a changing climate. Challenges remain for determination of in situ root-exudation rate and its response to FACE and warming.